2016
DOI: 10.1016/j.scitotenv.2015.11.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uncoated and citric acid coated cerium oxide nanoparticles, bulk cerium oxide, cerium acetate, and citric acid on tomato plants

Abstract: Little is known about the physiological and biochemical responses of plants exposed to surface modified nanomaterials. In this study, tomato (Solanum lycopersicum L.) plants were cultivated for 210days in potting soil amended with uncoated and citric acid coated cerium oxide nanoparticles (nCeO2, CA+nCeO2) bulk cerium oxide (bCeO2), and cerium acetate (CeAc). Millipore water (MPW), and citric acid (CA) were used as controls. Physiological and biochemical parameters were measured. At 500mg/kg, both the uncoated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
89
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 39 publications
13
89
1
1
Order By: Relevance
“…Differential CAT response in the shoots from kidney bean plants grown in soil with varying SOM contents validates that the CAT mimetic activity of CeO 2 is enhanced with more SOM in the growth media, due to stabilization of CeO 2 before entering the plants. In agreement with our observations in roots and leaves, Barrios et al (2015) found no effect on CAT activities in tomato plants exposed to pristine nano-CeO 2 ; however the CAT activity in the plants was increased upon exposure to more stable citric acid-coated CeO 2 . In barley leaves, CAT activity was not affected, but APOX activity increased significantly at 125-500 mg/kg nano-CeO 2 exposure in soil .…”
Section: Impact Of Nano-ceo 2 On Plant Growthsupporting
confidence: 92%
See 2 more Smart Citations
“…Differential CAT response in the shoots from kidney bean plants grown in soil with varying SOM contents validates that the CAT mimetic activity of CeO 2 is enhanced with more SOM in the growth media, due to stabilization of CeO 2 before entering the plants. In agreement with our observations in roots and leaves, Barrios et al (2015) found no effect on CAT activities in tomato plants exposed to pristine nano-CeO 2 ; however the CAT activity in the plants was increased upon exposure to more stable citric acid-coated CeO 2 . In barley leaves, CAT activity was not affected, but APOX activity increased significantly at 125-500 mg/kg nano-CeO 2 exposure in soil .…”
Section: Impact Of Nano-ceo 2 On Plant Growthsupporting
confidence: 92%
“…Similar to our observations in LOMS plants, previous studies on tomato, corn, cucumber and radish have also noted insignificant to slight increase in chlorophyll content on exposure to nano-CeO 2 (Wang et al, 2012;Zhao et al, 2013Zhao et al, , 2015Barrios et al, 2015;Zh). In another study, Rico et al (2015) showed that the chlorophyll content in barley leaves was increased at 125-500 mg/kg nano-CeO 2 , similar to our observations in LOMS leaves.…”
Section: Impact Of Nano-ceo 2 On Plant Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well recognized that the release of cerium oxide nanoparticles (CeO 2 NPs) into the environment could pose serious risks to human health due to their potential accumulation in food crops [1,2]. Previous investigations have shown that CeO 2 NPs could be taken up by radish (Raphanus sativus L) and many other agricultural crops [3][4][5][6][7][8] and the health risks associated with the foodborne Ce depend on the physicochemical properties of Ce in plant tissues [9,10]. A few previous studies reported that Ce in plant tissues remained as CeO 2 NPs after plant uptake [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These penetrating NPs were found to be transported both by symplastic and apoplastic modes and have shown xylem and phloem transport [23]. Furthermore, the role of NPs coating, such as with/without citrate [24], and surface charges [25,26] on plant uptake behaviour was also studied.…”
Section: Introductionmentioning
confidence: 99%